Antibiotic Reversal Activity of Piper longum Fruit Extracts against Staphylococcus aureus Multi-Drug Resistant Phenotype - Maryam Salah Ud Din; Umar Farooq Gohar; Hamid Mukhtar; Ibrar Khan; John Morris; Soisuda Pornpukdeewattana; S. Massa (Microbiology and Biotechnology Letters, 2023)
Maryam Salah Ud Din, Umar Farooq Gohar, Hamid Mukhtar, Ibrar Khan, John Morris, Soisuda Pornpukdeewattana, and Salvatore Massa. Microbiol. Biotechnol. Lett. 2023;51:432-40. https://doi.org/10.48022/mbl.2307.07012
Keywords: Piperaceae Chemical and Biological Studies; Essential Oils and Antimicrobial Activity; Banana Cultivation and Research